2018
DOI: 10.1016/j.polymer.2018.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive interphase analyses of isotactic polypropylene and cyanoacrylate with cobalt complex primers

Abstract: The modification of surface properties of isotactic polypropylene (it.PP) has attracted much attention in fundamental science and industrial applications. Primer treatment is a promising methods that is employed to overcome the poor adhesive property of it.PP. In this study, we examined the primer effect of the cobalt complexes, cobalt (II) acetylacetonate Co(acac)2 and cobalt (III) acetylacetonate Co(acac)3, from the perspectives of adhesive strength, curing process, surface structure, affinity between substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…These results suggested the correlation between T-peel strengths and interphase thicknesses. We have previously reported on the dependence of T-peel strength on interphase thickness and primer treatment . In this work, as the similar relation between T-peel strengths and interphase thicknesses without any primer treatment was observed, we suspected that the morphology and molecular behavior in the interphase region would have a large effect on their adhesive properties.…”
Section: Results and Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…These results suggested the correlation between T-peel strengths and interphase thicknesses. We have previously reported on the dependence of T-peel strength on interphase thickness and primer treatment . In this work, as the similar relation between T-peel strengths and interphase thicknesses without any primer treatment was observed, we suspected that the morphology and molecular behavior in the interphase region would have a large effect on their adhesive properties.…”
Section: Results and Discussionsupporting
confidence: 58%
“…The adhesive properties were decided by various factors including surface roughness of the adhered substrates, difference of surface free energies between substrates and adhesives, mechanical properties of adhesives and substrates, and adhesion interfacial structure. We also have previously reported on the correlation between adhesive strength and interfacial thickness of the isotactic polypropylene ( it .PP)/cyanoacrylate ester instant adhesives using a confocal Raman scattering microspectroscope . It is clarified that the primer treatment to it .PP substrates with cobalt complex primers provided a larger adhesive strength as well as a larger thickness of interfacial regions.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…The result showed that the synthesized samples were mostly irregular, with a particle size of less than 100 nm. For the case of Co(acac) 3 , the observation with SEM was not possible due to its magnetic nature as reported in previous work [95]. The porosity properties of SNW-1 nanoparticles were measured using N 2 physisorption at 77 K. In general, the SNW-1 sample demonstrates a property typical of microporous materials with type 1 isotherms, where high N 2 sorption was observed in a low-pressure region (Figure 4-4(a)).…”
Section: Characterization Of Snw-1 and Co(acac)mentioning
confidence: 94%